Análisis comparativo entre metodología ágil scrum y metodologías tradicionales para la gerencia de proyectos tecnológicos. - Quiroz Reyes, Jhon Washington (2022)
In recent decades, the advancement of information technologies and the continuous changes that have occurred have led to the question of whether the methods used until now, known as traditional (PMP, IPMA, PRINCE2, etc.), are the most suitable for directing projects. technological. Agile methodologies arose from this approach, focused on adaptability to changes, with self-organized teams, autonomy when making decisions and involvement of the user or client, the team and the interested parties. Although each project has its own characteristics and needs, different methods can be applied or different factors taken into account to have a greater probability of being successfully completed. Specifically, in technological projects, several factors have been found that help increase the chances of success. For this reason, in this case study, a bibliographic exposition of the agile and traditional methodologies in the management of technological projects is carried out, with the aim of making a comparison and obtaining which methodology would be more appropriate depending on the needs of the project.